The application of agricultural land rating and crop models to CO2 and climate change issues in Northern regions : the Mackenzie Basin case study - Brklacich, Michael; Curran, Patrick; Brunt, Douglas (Jokioinen : Agricultural Research Centre of Finland, 1996)
Selostus: Viljelyvyöhykkeiden ja kasvumallien soveltaminen ilmastonmuutoksen tutkimisessa: Mackenzien jokialue, Kanada